Pengaruh Bee Pollen terhadap kadar SGOT, SGPT dan gambaran histopatologis hepar pada tikus yang diinduksi pakan tinggi lemak - Sijani Prahastuti; Jeanny E Ladi; Kartika Dewi; Felicia Albertina; Muhammad K Imam (Journal of Medicine and Health, 2020)
Dyslipidemia is a risk factor for Non Alcoholic Fatty Liver Disease causing hepatocyte damage. Bee pollen has hypolipodemic, anti-inflammatory effects. The purpose of the study was to analyze the effects of Bee Pollen on the levels of SGOT, SGPT, and its effects on the liver’s histopathologic. The experimental laboratory research method, 30 rats divided into 6 groups (n = 5). HFD was given for 28 days, Simvastatin and Bee Pollen were given from 15 until 28 days. SGOT, SGPT were examined at 0, 15, 29 days by spectrophotometry (340 nm). Histopathological liver examination at 29 days. Results: The levels of SGOT, SGPT between Bee pollen 1 (18 mg/kgBW/day), 2 (36 mg /kgBW/day), 3 (72 mg /kgBW/day) with HFD were very significant differences. The levels of SGOT Bee Pollen 1,2,3 compared to simvastatin were not significantly different. SGPT Bee Pollen 3 levels compared to simvastatin there were no significant differences. Measurement of the degree of cloudy swollen cells, portal inflammation, bridging fibrosis, periportal fibrosis between Bee Pollen 1, 2 with HFD there is a significant difference, Bee Pollen 3 and HFD differ very significantly. Conclusion: Bee Pollen can reduce levels of SGOT, SGPT, its potential effects is equivalent to simvastatin on reducing levels of SGOT, SGPT and improved the histopathological image of the liver on male rats wistar induced by high-fat diet. . Keywords : Dyslipidemia, SGOT, SGPT, Bee pollen, Histopatological Image